Situated learning to develop critical thinking in Higher Pedagogical Education students - Alcarraz Carbajal, Bibiano (2024)
Applied educational research aimed to determine the influence of situated learning on the development of critical thinking in Higher Pedagogical Education students. To this end, an experimental study was carried out, with a quasi-experimental design, which involved 192 students, selecting a sample of 56 students through a non-probabilistic sampling method. This sample was divided equally into two groups: experimental and control, each consisting of 28 students. Data collection was carried out using a pedagogical test composed of 30 items. The hypothesis evaluation was carried out using the Mann-Whitney U test. The results showed that the situated learning strategy significantly affects the development of analysis, explanation, inference, interpretation, evaluation and self-regulation capacities in the development of students' critical thinking (p=0.000<0.05).